TESTING OF SEALING ELEMENTS FOR FIB-1 APPARATUS DESIGNED TO LIQUIDATE OPEN ERUPTION BY DRILLING TOOLS - Bujok, Petr; Klempa, Martin; Ryba, Jakub; Porzer, Michal; Šancer, Jindřich (GeoScience Engineering, 2018)
Petroleum and natural gas still have their place among the most important resources in many industrial areas. Their global consumption influences an increasing demand on the quality of drilling works and the efficiency of extraction. Nonetheless, even in this field of human activity, we can encounter exceptional events and accidents. One of the most serious kinds of accidents during exploration is the so-called open eruption of the extracted medium. The specific case of this accident is an open eruption caused by drilling tools when a working crew is not capable of securing drilling workplace. In order to solve this emergency situation, Main Mining Rescue Station Hodonin (Hlavní báňská záchranná stanice v Ostravě, HBZS), located in Lužice, in cooperation with researchers from Department of Geological Engineering at Faculty of Mining and Geology, VŠB - Technical University of Ostrava, designed and developed specialised apparatus DPRP (Drill Pipe Rescue Press), working designation FIB-1. This apparatus enables the liquidation of eruption by pressing the drilling rod. The residual crack, which remains following the pressing, must be eliminated by sealing materials. This paper reviews the testing of sealing elements, designed by our team, in a residual crack of circle shape with the help of press machine MTS 816 Rock Test System. Keywords: pressure signs; eruption; liquidation apparatus; sealing elements https://doi.org/10.2478/gse-2018-0012